2017
DOI: 10.3390/su9081454
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Wind Power in China: Status and Future

Abstract: Due to the rapid economic development in China, the conflict between the increasing traditional energy consumption and the severe environmental threats is more and more serious. To ease the situation, greater use of wind energy in China could be the solution for energy conservation and sustainable environment in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…2) Southwest Highland: Highland area with medium precipitation, lack of wind. 3) Northeast China: Plenty of wind [28], no monsoon and lack of precipitation.…”
Section: A Results Of Community Detectionmentioning
confidence: 99%
“…2) Southwest Highland: Highland area with medium precipitation, lack of wind. 3) Northeast China: Plenty of wind [28], no monsoon and lack of precipitation.…”
Section: A Results Of Community Detectionmentioning
confidence: 99%
“…An avalanche of studies [4][5][6][7] has identified greenhouse gases(GHGs) as a major contributor to global warming with energy-related GHGs accounting for majority of total GHGs. Emissions from consumption of coal [8], natural gas, petroleum products and other GHG-emitting sources of energy has contributed to the hefty weight of energy-related GHGs to total GHG. Due to the emission-free and sustainable [9][10][11][12][13] characteristics of renewable-and-sustainable sources of energy (RSSE), increasing the share of RSSEs in future energy-mix [8] dominates the submitted Intended Nationally Determined Contributions (INDCs) of parties to the 2015 Paris accord.…”
Section: Introductionmentioning
confidence: 99%
“…Emissions from consumption of coal [8], natural gas, petroleum products and other GHG-emitting sources of energy has contributed to the hefty weight of energy-related GHGs to total GHG. Due to the emission-free and sustainable [9][10][11][12][13] characteristics of renewable-and-sustainable sources of energy (RSSE), increasing the share of RSSEs in future energy-mix [8] dominates the submitted Intended Nationally Determined Contributions (INDCs) of parties to the 2015 Paris accord. New technologies for renewable energy generation such as the wave energy linear generator proposed by Franzitta et al [14] are paramount to achieving energy independence.…”
Section: Introductionmentioning
confidence: 99%
“…The wind power could help with emissions reduction and energy conservation [3]. And the wind energy is abundant in China due to its vast land and long coastline [3]. It is clearly to find that the wind power is a sustainable and clean generation with environmentally friendly production using green and renewable energy [4][5][6], then it is essential to promote this generation for adjusting the coal-dominant energy structure and realizing the low-carbon society.…”
Section: Introductionmentioning
confidence: 99%
“…As for the wind power, it is a clean and renewable energy for power generating. The wind power could help with emissions reduction and energy conservation [3]. And the wind energy is abundant in China due to its vast land and long coastline [3].…”
Section: Introductionmentioning
confidence: 99%